PERKEMBANGAN BATIK GETAH GAMBIR LUMPO PESISIR SELATAN (STUDI DESKRIPSI DI RUMAH BATIK LUMPO) - Ikbal Rahdianto; Erwin Erwin (Serupa The Journal of Art Education, 2021)
Batik Getah Gambir Lumpo is the signature batik of the lumpo batik in the Ampuan Lumpo sub-district which was founded in 2013 and was inaugurated in 2017. The sap-gambir lumpo batik has a characteristic motif with contemporary concepts.Novia Hertini, the owner, revealed that the existence of this lumpo batik sap could empower the surrounding community to create jobs and be useful for increasing economic development around the village of Ampuan Lumpo, Pesisir Selatan, West Sumatra.With the main ingredient in the form of sap Gambir, the gatah farmer also feels the presence of this lumpo sap gambir batik. And the sap of gambir lumpo batik is well known among many circles, especially in the government agencies which have given awards to the batik sapah gambir lumpo house in 2020.